(untitled) (Economics and region, 2025)
The article comprehensively analyzes contemporary issues in commodity studies as a multidisciplinary scientific field that combines applied and theoretical knowledge from the natural, technical, and social sciences. It is emphasized that commodity studies play an important role in ensuring a systematic approach to assessing the quality, safety, consumer characteristics, and environmental safety of goods, which is the basis for the effective functioning of modern markets. Particular attention is paid to a number of key systemic challenges facing the industry: the lack of unified and up-to-date quality standards, which complicates the classification and identification of goods; rapid technological and digital transformations which are changing traditional approaches to quality control, logistics, and consumer interaction; environmental threats caused by growing demands for sustainable production and consumption; reduced consumer awareness, which exacerbates the problem of information asymmetry between producers, sellers, and end consumers, as well as market globalization. The article analyzes current trends in the implementation of digital technologies in commodity studies, in particular the use of blockchain to ensure supply chain transparency, the application of artificial intelligence to automate quality control, and the analysis of large volumes of data (Big Data) to predict consumer trends. It has been shown that the integration of such technologies contributes to improving the efficiency of commodity flow management, reducing the risk of counterfeiting, and improving consumer confidence. It has been proven that modern commodity studies go beyond the traditional expert and analytical functions, becoming a strategic factor in the formation of a sustainable, innovative, and competitive commodity market. Emphasis was placed on the need to review existing methodological approaches to the classification and identification of goods, taking into account digital and environmental challenges. The study resulted in recommendations for strengthening interdisciplinary cooperation in commodity studies, introducing innovative technologies, and developing the regulatory framework, which will create conditions for the sustainable development of the commodity market in the context of modern global challenges.